ECONOMICS OF GERBERA UNDER POLYHOUSE CULTIVATION IN RANGA REDDY DISTRICT OF TELANGANA STATE - R. VIJAYA KUMARI and K. SUPRIYA, V.V.D. MANISHA, T. LAVANYA (The Journal of Research, PJTSAU, 2021)
India has been predominantly an agrarian country where majority of farmers use traditional farming techniques. Traditional farming has always been riskydue to unpredictable weather conditions and exposure to pests and diseases. Moreover, in recent years’ climate change has become biggest challenge. To meet the food requirements of growing population, crops have to be cultivated under protected conditions without depending upon the external climatic conditions. Thus, protected cultivation assumed lot of significance in recentyears.